Embryonic development of Girardia tigrina (Girard, 1850) (Platyhelminthes, Tricladida, Paludicola) - Vara,DC. (2008)
The embryonic development of freshwater triclads is mainly known from studies of species of Dendrocoelum, Planaria, Polycelis, and, more recently, Schmidtea. The present study characterizes the development of Girardia tigrina (Girard, 1850) by means of optical microcopy using glycol methacrylate semi-thin sections. 94 cocoons were collected in the period from laying to hatching, with intervals of up to twenty-four hours. The sequence of morphological changes occurring in the embryo permitted the identification of nine embryonic stages. At the time of cocoon laying, numerous embryos were dispersed among many yolk cells, with a rigid capsule covering the entire cocoon. In the first stage (approx. up to 6 hours after cocoon laying), yolk cells and embryonic cells showed random distribution. Stage II (between 12 and 24 hours after cocoon laying) is characterized by aggregates of blastomeres, which later aggregate forming an enteroblastula. Approximately 2 days after cocoon laying (stage III), formation of the embryonic epidermis and embryonic digestive system took place, the latter degenerating during the subsequent stage. Stage V (until the fourth day) is characterized by the formation of the definitive epidermis. Between 4 and 6 days after laying, organogenesis of the definitive inner organs starts (stage VI). Approximately 14 days after laying (stage IX), formation of the nervous system is completed. At this stage, the embryo shows similar characteristics to those of newly hatched juveniles. The hatching of Girardia tigrina occurs in the period between twelve to twenty-two days after cocoon laying.